Energy-Efficient Routing Algorithms For Wireless Sensor Network - Goh, Hock Guan (2006)
In this project, the author has carried out a study on the performance of various routing algorithms applied to a two-dimensional grid topology wireless sensor network. The study focuses on collecting sensor data from the sensor nodes to a base station with minimum energy consumption and minimum network delay in a flat-tree network. To achieve the objectives, the author proposes two routing algorithms, called the Tree-Based Routing Algorithm and the Information Selection Branch Grow Routing Algorithm (ISBG).